2022
DOI: 10.1111/fcp.12760
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulator FTY720 improves glucose homeostasis and diabetic complications by rejuvenation of β‐cell function in nonhuman primate model of diabetes

Abstract: Inadequate β-cell mass is essential for the pathogenesis of type 2 diabetes (T2D). Previous report showed that an immunomodulator FTY720, a sphingosine 1-phosphate (S1P) receptor modulator, sustainably normalized hyperglycemia by stimulating β-cell in vivo regeneration in db/db mice. We further examined the effects of FTY720 on glucose homeostasis and diabetic complications in a translational nonhuman primate (NHP) model of spontaneously developed diabetes. The male diabetic cynomolgus macaques of 18-19 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Meanwhile, our data showed that the fasting insulin and concomitant C‐peptide in the HGM monkey were still within common level. Some reports also showed no difference with the insulin and C‐peptide between spontaneously diabetic and non‐diabetic monkeys, 16,27 but some reports are contradictory 15,23,28‐30 . The primary reason is likely that the insulin maintains normal at early stage of T2DM, whereas it increases to compensate the insulin resistance later and ultimately decreases or does not express because of β‐cells dysfunctions 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our data showed that the fasting insulin and concomitant C‐peptide in the HGM monkey were still within common level. Some reports also showed no difference with the insulin and C‐peptide between spontaneously diabetic and non‐diabetic monkeys, 16,27 but some reports are contradictory 15,23,28‐30 . The primary reason is likely that the insulin maintains normal at early stage of T2DM, whereas it increases to compensate the insulin resistance later and ultimately decreases or does not express because of β‐cells dysfunctions 29 .…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 improves glucose homeostasis in non-obese diabetic (NOD) mice, in db/db mice, and a in non-human primate model of spontaneous diabetes (NHP) [ 8 , 9 , 10 ]. Moreover, this compound promotes lipolysis activation and prevents obesity in a high-fat diet (HFD) mouse model [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these findings, the administration of FTY720 also improved cardiac dysfunction and decreased fibrosis in recent independent studies using animal models of genetically induced hypertrophic cardiomyopathy and in myocardial ischemic/reperfusion [ 5 , 6 , 7 ]. The administration of FTY720 favorably influences glucose sensitivity in non-obese diabetic mice (NOD), in db/db mice, and in a non-human primate model [ 8 , 9 , 10 ]. Moreover, it promotes lipolysis upon consumption of a high-fat diet (HFD) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to FTY720 significantly reducing CD4+ T and CD8+ T lymphocytes and increasing dendritic cells, thereby preventing islet β cells from being destroyed by autoimmune cells and improving glucose homeostasis. 29 …”
Section: Introductionmentioning
confidence: 99%
“…This may be due to FTY720 significantly reducing CD4+ T and CD8+ T lymphocytes and increasing dendritic cells, thereby preventing islet β cells from being destroyed by autoimmune cells and improving glucose homeostasis. 29 In addition to protecting islet β cells function, FTY720 also improved glucose tolerance and insulin sensitivity in obese and insulin-resistant rodent models. In diet-induced obesity mice, FTY720 treatment can prevent weight gain, improve insulin sensitivity, and reduce lymphocytes and macrophages in adipose tissue.…”
Section: Introduction To Fty720mentioning
confidence: 99%